Bacterial community succession and metabolite changes during doubanjiang-meju fermentation, a Chinese traditional fermented broad bean (Vicia faba L.) paste. (1st March 2017) - Li, Zhihua; Rui, Junpeng; Li, Xiangzhen; Li, Jiabao; Dong, Ling; Huang, Qiaolian; Huang, Chi; Wang, Zipeng; Li, Lu; Xuan, Pu; Tang, Yuming; Chen, Fusheng
Highlights: Dynamics of bacterial populations in the doubanjiang-meju fermentation were revealed. Major fermentation metabolites were identified using 1 H-NMR method. Relationships between bacterial community and metabolites were established. Abstract: Doubanjiang-meju, a major ingredient of Chinese fermented food for several centuries, is produced using broad bean, wheat flour and salt. In this study, we investigated prokaryotic community succession and metabolite changes using high-throughput sequencing and 1 H-NMR methods. After 35 days, bacterial communities, except Lactobacillus and Acinetobacter, were relatively stable until the end of fermentation, and consisted predominantly of the genera Tetragenococcus, Lactobacillus, Staphylococcus, Acinetobacter, Pseudomonas and Streptococcus . Glucose, arabinose, fructose and mannitol were identified as major sugars, lactate and acetate as major organic acids, and amino acids as the major nitrogen compounds present in doubanjiang-meju. Correlation analysis revealed important links between bacterial populations and metabolites, e.g., Pseudomonas was significantly correlated with 10 nitrogenous metabolites, while Streptococcus was significantly correlated with six carbonic metabolite and eight nitrogenous metabolites. These results not only revealed bacterial succession and dynamic changes in metabolites as well as pH and color, but also elucidated their relationships during the doubanjiang-meju fermentation.